To Touch or Not to Touch: Taxidermy and the Museum - Ann C. Colley (ESPES, 2025)
Recently I attended a class in which a conservation specialist instructed the students to practice caution when treating an old piece of taxidermy. She directed them to wear masks and don protective gloves. Treating the taxidermy with naked hands was strictly forbidden. Upon hearing the instructor’s cautionary words, I wondered why taxidermy, once considered beautiful and desirable, had now become a toxic site. What had occasioned the change? And what does this alteration have to say about the nature of our contemporary relationship to our surroundings. And what does it have to say about the nature of touch? This essay is divided into four parts. The first considers former opportunities to reach out and actually touch taxidermy. This section discusses the nature of touch, particularly its affirmation of reality. The second section attends to the necessity of protecting taxidermy from insect infestations, a concern that until the 1980s, involved using large doses of arsenic and mercuric chloride. The third section discusses how the application of these toxics has recently alarmed museum directors. No longer is one allowed to touch the displayed taxidermy. Part Four addresses this alteration. The shift from welcoming touch to banning it participates in a society in which touch is often feared or deemed unnecessary. Touching the genuine article has been replaced by virtual realities or mediated so that a skin to skin encounter is now not as available. This alteration has compromised the experience of touch and our relationship to the world.